The Influence of Social Media Use Intensity and Interpersonal Communication Style on Self-Image Formation among Adolescents and Young Adults in the Digital Environment - Bryna Callista; Syahwa At Taric Romadhona; Elisabeth Robeka Maniagasi; Eko Budi Siswandoyo; Novi Ratriningtyas (oneamd.com, 2025)
The formation of self-image in the digital environment refers to the process by which individuals manage their appearance, self-perceptions, and social interactions through social media in order to obtain social recognition. This study aims to examine the influence of social media use intensity and interpersonal communication style on self-image formation among adolescents and young adults in the digital space. A quantitative research approach was employed using a survey method involving 144 respondents aged between 13-30 years old who actively use social media platforms. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression analysis. The findings indicate that both the intensity of social media use and interpersonal communication style have a positive and significant effect on self-image formation, both partially and simultaneously. These results suggest that active engagement in social media, supported by effective interpersonal communication styles, plays a crucial role in shaping individuals’ self-image in digital environments.